Carbon monoxide absorption with iron and alcohol solutions via design expert method - Kandilci, Hava Gizem; Ozgunduz, Hediye Irem; Acarali, Nil; Gulen, Jale (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2022)
In this study, effective parameters on CO absorption using ethyl alcohol and iron solutions [time (15-75 min), temperature (36-40 degrees C), concentration (0-40% v/v, of ethyl alcohol, 0-8%w/v, of iron solution), stirring rate (0-400 rpm)] and interactions of parameters with each other have been examined as the optimization method by using Design Expert method, 4 parameters and 5 levels. Mathematical optimization results are evaluated by finding the optimum points. As a result, the effects of parameters on CO absorption are comparatively investigated. It is observed that the parameters could interact binary and also influence CO absorption (R1). According to ANOVA analysis, the value of the quadratic model (p<0.0001) is found to be less than 0.05 and indicates that the model is meaningful for ethyl alcohol solution. The experimental data of the model is well represented for ethyl alcohol solution (R2=0.9426) and iron solution (R2=0.9384) as can be seen from correlation coefficients. The data are furnished via FT-IR spectra.
Keywords: Absorption; Carbon monoxide; Design Expert; Optimization; NANOPARTICLES; INHALATION; PROTECTION; INJURY; CO; Chemistry; Engineering